2013
DOI: 10.1007/s00702-013-0989-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypoxanthine, antioxidants and allopurinol on cholinesterase activities in rats

Abstract: In the present study, we investigate the in vitro effect of hypoxanthine on acetylcholinesterase and butyrylcholinesterase activities in the hippocampus, striatum, cerebral cortex and serum of 15-, 30- and 60-day-old rats. Furthermore, we also evaluated the influence of antioxidants, namely α-tocopherol (trolox) and ascorbic acid, and allopurinol to investigate the possible participation of free radicals and uric acid in the effects elicited by hypoxanthine on these parameters. Acetylcholinesterase and butyryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Previous studies suggest that purine metabolites might be involved in the pathophysiology of AD (Xiang et al, 2015), which was also proved in current models. In addition, hypoxanthine could enhance acetylcholinesterase activity in the hippocampus (Wamser et al, 2013), which decreases acetylcholine levels and is closely related to the pathophysiology of AD. Moreover, hypoxanthine has also been reported to induce oxidative stress in rat striatum, which is vital to the pathogenesis of AD and will impair brain memory of mice (Bavaresco et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that purine metabolites might be involved in the pathophysiology of AD (Xiang et al, 2015), which was also proved in current models. In addition, hypoxanthine could enhance acetylcholinesterase activity in the hippocampus (Wamser et al, 2013), which decreases acetylcholine levels and is closely related to the pathophysiology of AD. Moreover, hypoxanthine has also been reported to induce oxidative stress in rat striatum, which is vital to the pathogenesis of AD and will impair brain memory of mice (Bavaresco et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This could lead to the accumulation of hypoxanthine [31] . It was reported that hypoxanthine enhanced acetylcholinesterase (AChE) activity in the hippocampus and striatum of 15- and 30-d-old mice, when added to the incubation medium [32] . AChE is associated with the pathophysiology of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxanthine is another purine compound that implicated in AD progression. Acetylcholinesterase is closely associated with AD pathophysiology and hypoxanthine could enhance acetylcholinesterase activity when it is added to incubation medium [39]. Constant stimulation of acetylcholinesterase activity might reduce acetylcholine levels, an essential neurotransmitter of central nervous system, and hypoxanthine therefore contributes much to memory deficits by acetylcholinesterase-related mechanism.…”
Section: Purine Metabolismmentioning
confidence: 99%